Sociodemographic Background and Psychosocial Behaviors of Perpetrators of Intimate Partner Violence: A Hospital-based Retrospective Study - Amal Nishantha Vadysinghe; Tharanga Bandara Nayakarathne; Y. M. G. Ilangarathna Banda; Kasun Bandara Ekanayake; Isuru Perera; Yomal Wijesiriwardena (Wolters Kluwer Medknow Publications, 2024)
Background: Intimate partner violence (IPV) is a worldwide issue with a high prevalence rate seen in Asia. Aims and Objectives: To plan and implement preventive measures, it is important to understand the characteristics, background, and medico-legal significance, especially from the perspective of perpetrators. MATERIALS AND METHODS: This study is a questionnaire-based retrospective study conducted among perpetrators of IPV who presented to a tertiary care hospital in Sri Lanka. Results: Out of 325 subjects, 97.2% were males and 64.0% were aged 26-45 years. Most (80.9%) perpetrators were older than the victimized partner, with a mean age gap of 4.3 years. Only 2.8% had achieved higher education and 78.5% had been married to the victim for more than5 years. Alcohol and/or other substances were abused by 75.4% and 11.1% of them were diagnosed with a psychiatric illness. Perpetrators have been exposed to child abuse (CA) as minors (50.1%), with physical CA being the most common, whereas 42.5% had witnessed IPV during their childhood. Ill-treatment by the spouse (odds ratio [OR] = 24 [95% confidence interval (CI):5.6, 99.9]) and substance use (OR =22 [95% CI: 5.1, 91.5]) were significantly associated with perpetrating emotional violence. A victim having an extramarital affair was 5.1 times more likely to be subjected to sexual IPV, whereas previous IPV, parental deprivation, and affairs of perpetrator were proved to be protective factors. IPV had negatively affected the economy of 71.3% of families. Legal procedures were expected by 22.4%, whereas 60% wanted to negotiate with their spouses. Conclusion: Families having low income and alcohol/substance abuse should be targeted to plan preventive programs at the community level. Proper counseling and follow-up of victims of CA can be used as a primary preventive measure of IPV.